1991
DOI: 10.1111/j.1651-2227.1991.tb11860.x
|View full text |Cite
|
Sign up to set email alerts
|

More Than Half the Sporadic Cases of Hemophilia A in Sweden Are Due to a Recent Mutation

Abstract: The aim of this study was to ascertain how many of the sporadic cases of severe Haemophilia A in Sweden are due to recent mutation, and establish its origin. DNA analysis was performed in 18 randomly selected families with a sporadic case of severe haemophilia A. Restriction fragment length polymorphism (RFLP) patterns were investigated, two intragenic (Bc1 I, Xba I/Kpn I) and two extragenic (DX 13, St 14) RFLP being used. In 10/18 families a haemophilia-linked gene was found to have derived from the healthy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…In this study, 24 mothers and 9 sisters of patients with HA in whom mutations were found were analyzed for carrier potential. The mothers of seven patients were carriers, and we confirmed that two-thirds of HA mutated alleles were transmitted from normal females [29].…”
Section: Discussionsupporting
confidence: 66%
“…In this study, 24 mothers and 9 sisters of patients with HA in whom mutations were found were analyzed for carrier potential. The mothers of seven patients were carriers, and we confirmed that two-thirds of HA mutated alleles were transmitted from normal females [29].…”
Section: Discussionsupporting
confidence: 66%
“…In Sweden, haplotype analysis of a random sample of families with isolated, severe hemophilia A, suggested that at least 55% of mutations were sporadic occurrences within the past two generations [38]. In the current series, there was no family history of hemophilia in 70% of families whose affected members had severe and moderately severe hemophilia A.…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown that mothers of a sporadic case very often carry a de novo mutation and that the X-chromosome that carries the mutation often is derived from the sporadic boy's healthy maternal grandfather. 11,12 Thus, sisters to mothers of a sporadic case are often noncarriers. However, the extent of our knowledge today certainly does not allow us to exclude carriership in sporadic families.…”
Section: Genotype Assesment-direct Gene Analysismentioning
confidence: 99%